Про єдиність унітального дільника матричного многочлена над довільним полем - Прокіп, В.М. (Український математичний журнал, 1993)
Conditions are established under which the unital divisor extracted from a matrix polynomial over an arbitrary field is determined uniquely by its characteristic polynomial. The result obtained is applied to the problem of solving matrix polynomial equations.